Validation of The Satisfaction Assessment Tool Among University Graduates - Ma. Erenita V. Bahian (Alliance of Health Activists (AloHA), 2019)
It is important to assess the level of satisfaction among university students because research findings linked satisfaction with academic performance. This study aims to validate the level of satisfaction assessment tool, which would measure the characteristics of the instrument. The respondents were 231 students of the university. The data were collected using a survey questionnaire. Exploratory factor analysis and descriptive statistics were the methods utilized. Estimation of main components of the analysis utilized the Varimax rotation method, extraction of factors used eigenvalues greater than one, and for selection of items. Reliability of assessment tool was measured with the use of Cronbach’s alpha. The analysis resulted three factors which explained 51.7% of the total variance. The three factors were: Personal and Professional satisfaction, Student Support satisfaction and Instruction-related satisfaction. The reliability of the scale was α = .861, and its factors were 0.810, 0.753, and 0.717, respectively. These were within the minimum acceptable value. Results showed that the scale was reliable and valid tool to determine the level of satisfaction among university students. Keywords: Student’s satisfaction, Factor analysis, Reliability, Validity